TEACHING WRITING DESCRIPTIVE PARAGRAPHS THROUGH OPINION FINDERâ€™S TECHNIQUE TO THE EIGHTH GRADE STUDENTS OF TRI DHARMA JUNIOR HIGH SCHOOL OF PALEMBANG - Noviati Noviati (Esteem Journal of English Education Study Programme, 2018)
Abstract:The main problem of this study was â€œIs it effective to teach writing descriptive paragraph through opinion finderâ€™s technique to the eighth grade students of Tri Dharma Junior High School of Palembang?â€ The objective of this study is to find out whether or not it is effective to Teach Writing Descriptive Paragraph through Opinion Finderâ€™s Technique to the Eighth Grade Students of Tri Dharma Junior High School of Palembang. The population of this study was all of the Eighth Grade Students of Tri Dharma Junior High School of Palembang. The total number of the population was 166 students from five classes. The sample was 32 students taken from VIII.E class by using cluster random sampling. Pre- experimental method was used in this study. In collecting the data the writer used written test and then the data was analyzed by using Matched t-test. Based on the data analysis from the test, it was found that teaching writing writing descriptive paragraph through opinion finderâ€™s technique to the eighth grade students of Tri Dharma Junior High School of Palembang was effective. The average score in the pre-test was 67 and the average score in the post-test was 73 the result of calculation of method t-test was 7.5. Therefore, teaching writing descriptive paragraphs through opinion finders technique to the eighth grade students of Tri Dharma Junior High School of Palembang was effective in increasing students ability especially in writing descriptive paragraph.